No more pounding - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Mechanics in Benin and Togo have adapted simple crushing machines, first designed in Europe, for small-scale food processing. There is a hand-driven mechanical one and an electric one, powered by a dynamo. They can be used by women to crush and...